2019
DOI: 10.1007/s00705-018-04129-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adenovirus, papillomavirus and parvovirus in Brazilian bats of the species Artibeus lituratus and Sturnira lilium

Abstract: Bats play a significant role in maintaining their ecosystems through pollination, dispersal of seeds, and control of insect populations, but they are also known to host many microorganisms and have been described as natural reservoirs for viruses with zoonotic potential. The diversity of viruses in these animals remains largely unknown, however, because studies are limited by species, location, virus target, or sample type. Therefore, the aim of this study was to detect fragments of viral genomes in bat sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The results showed that the sequences identified in this study are monophyletic and belong to the same CHPV lineage because they have 96% of identity in the NS1 gene region. Phylogenetic trees also show that the closest CHPV to our sequences are closely related with sequences previously identified in hematophagous Desmodus rotundus bats in southeast Brazil [ 40 ] and insectivorous Artibeus lituratus bats from South Brazil [ 72 ]. The median identity between our sequences and the Desmodus rotundus CHPV is 76%.…”
Section: Discussionsupporting
confidence: 74%
“…The results showed that the sequences identified in this study are monophyletic and belong to the same CHPV lineage because they have 96% of identity in the NS1 gene region. Phylogenetic trees also show that the closest CHPV to our sequences are closely related with sequences previously identified in hematophagous Desmodus rotundus bats in southeast Brazil [ 40 ] and insectivorous Artibeus lituratus bats from South Brazil [ 72 ]. The median identity between our sequences and the Desmodus rotundus CHPV is 76%.…”
Section: Discussionsupporting
confidence: 74%
“…Limitations of the current work emerge from uncertainty concerning the direction of associations among the host's immune response, shifts in gut microbial composition and pathogenic impacts (Hooks & O'Malley, 2017). We cannot rule out that the associations with MHC and pathogen resistance stem from linked genes that, for instance, affect physiology, thus altering conditions in the gut and influence the abundance of specific gut microbes and microbiota-mediated (Canuti et al, 2011;Finoketti et al, 2019), the immune system and microbiota are probably challenged by other parasites than just AstV, which, in turn, might blur links between the MHC, microbial diversity and AstV infection. Additionally, our nondestructive, low-impact AstV assessment cannot address the prolonged impacts recent infections have on the microbiota of recovering bats.…”
Section: Discussionmentioning
confidence: 92%
“…A factor heedlessly ignored in this ménage ‐ à ‐ trois are co‐infections. Particularly in a bat family frequently infected with multiple parasites (Canuti et al, 2011; Finoketti et al, 2019), the immune system and microbiota are probably challenged by other parasites than just AstV, which, in turn, might blur links between the MHC, microbial diversity and AstV infection. Additionally, our nondestructive, low‐impact AstV assessment cannot address the prolonged impacts recent infections have on the microbiota of recovering bats.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviruses have been detected in bats from several countries including Italy, Germany, China, and Hungary, however, the number of different adenoviruses detected in bats is small [ 36 , 40 , 81 , 82 , 106 , 107 ]. The genus Mastadenovirus has been thought to infect only mammals, including humans [ 36 , 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%